Development of the electronic physics textbook for students of secondary school - Prutko, A.S.; Kudussov, A.S.; Mussenova, E.K.; Kambarova, Zh.T. (KU Publ., 2020)
The work the results of using the developed electronic textbook on physics for organizing the independent work of secondary school students is analyzed. The possibilities of an electronic textbook are shown, the advantages of using the textbook in the learning process are noted. For the development of the electronic textbook, the C# programming language was used in the Microsoft Visual Studio software environment. The main idea of developing an electronic textbook is the relationship between theoretical teaching and practical skills. The electronic textbook provides two modes of operation: training mode and control mode, thus the electronic textbook contains a block of theoretical material and a module for interactive testing of students' knowledge. The theoretical material of the textbook has been developed in accordance with the standard curriculum for the subject “Physics”. The interactive testing module includes standard physical problems of different degrees of complexity, as well as practice-oriented problems on physics. A set of practice-oriented problems has been developed, the use of which in the process of teaching physics will allow to ensure the formation of students' theoretical knowledge and practical skills, to prepare students for practical activities. The main advantage of an electronic textbook is interactivity. The novelty of the development of an electronic textbook is implementation in accordance with a new approach aimed at shaping students' knowledge about the practical applications of physics and developing their practical skills.
Орта мектеп оқушылары үшін физика пəні бойынша электрондық оқу құралын əзірлеу
Разработка электронного учебного пособия по физике для учащихся средней школы
Keywords: electronic textbook; information and communication technologies; interactive testing; physical problems; pedagogical experiment